Structural heterogeneity and functional convergence of transposable elements - Kosovsky, Gleb Yu.; Glazko, Galina V.; Glazko, Tatiana T. (Frontiers in Genetics, 2025)
Almost half the mammalian genomes consist of transposable elements (TEs) and their derivatives. The distribution density of TEs can be associated with genomic regions of chromosomal rearrangements in different mammalian species and with the genomic localization of protein-coding genes that differ in length and function. To evaluate these characteristics at the local genomic level, an analysis of the distribution of various TEs (retrotransposons and DNA transposons) was performed in three mammalian species (human, cattle, and domestic rabbit) in genes with different functions and chromosomal localizations and their flanking regions. In humans and rabbits, melanophilin (MLPH) and myostatin (MSTN) are syntenic, but not in cattle. In the latter, MLPH and the leptin receptor (LEPR) are syntenic, but not in humans and rabbits. The alpha-thalassemia gene is always located on chromosome X. The results indicate that the frequencies of different TEs are species-specific and do not depend on the length of genes, their function, or chromosomal localization. There were also species-specific differences in the ratio of “ancient” and “young” short interspersed nuclear elements (SINEs) and long interspersed nuclear elements (LINEs). There was a statistically significant positive correlation between ancient SINE + LINE and LTR-ERV (p < 0.01) and a significant negative correlation between young SINE + LINE and DNA transposons (p < 0.05). Competitive relationships between TEs are probably defined by the presence of identical regulatory motifs in different TEs, associated with the reliance of TE amplification on the host’s own regulatory systems.